Computer-aided diagnostic system for the prediction of ventricular tachycardia using ECG signals - Teo, Nicholas Weijie (Nanyang Technological University, 2024)
Ventricular Tachycardia (VT) is a type of arrhythmia caused by disturbances in the electrical activities originating in the ventricles of the heart. Although it is usually harmless when a VT episode occurs for a short period of time, it is often linked to various underlying cardiac conditions such as Coronary Artery Disease (CAD) or Valvular Heart Diseases. Prolonged and sustained VT episodes could also potentially lead to life threatening conditions such as Ventricular Fibrillation (VF).